Arctic food biographies. An ethnographic study of food and health in everyday life of elderly Arctic women - Kvitberg, Trine (UiT The Arctic University of Norway, 2020)
The aim of the ethnographic study described was to listen sensitively and give voice to elderly Arctic women’s personal food biographies and everyday experiences of living in small coastal towns and inland areas of Norway’s Circumpolar North, North West Russia and Greenland. These specified geographical contexts were selected because they have been the focus of the Arctic and Global Health research activities at the University of Tromso (UiT) on food, health and sociocultural changes in the Arctic. The focal point of the ethnographic research described in this thesis is indigenous women’s everyday life experiences on food and health in an Arctic context. Ethnographic interviews were conducted with the participants in their Arctic kitchens. They involved personal encounters with 16 story tellers who, in a positive manner, substantiated the themes in the written accounts. Three detailed personal stories are featured in this dissertation. In the evaluation of these ethnographic interviews, attention is paid to how the participants tell their stories and express their health and wellbeing in everyday life through their personal food biographies. The interviews demonstrate a confluence of practices and among them eating traditional food is a key factor to everyday life, health and well-being. The thesis is written from a critical medical anthropological perspective. This perspective gives voice to individual experiences and the consequences that social forces (political, economic, cultural, institutional and religious) can inflict on human experience. These perspectives influenced the form of the interviews and account for why they turned personal. This allows the reader to be touched by the personal stories. The thesis illustrates how colonization expresses itself in the form of bodily pain in the individual body. It is demonstrated that researchers methodologically can recognize and experience such embodied experiences of pain by establishing trust in relation to the participants and listening sensitively to words, ...